P493 Cost-effectiveness of venous thromboembolism prophylaxis after hospitalization in patients with Inflammatory Bowel Disease. (27th May 2021) - Lee, K; Lim, F; Colombel, J F; Hur, C; Faye, A
Abstract: Background: Patients with inflammatory bowel disease (IBD) have a 2- to 3-fold greater risk of venous thromboembolism (VTE) than the general population, with increased risk during hospitalization. However, recent evidence suggests that this increased risk persists post-discharge. As such, we aimed to determine the cost-effectiveness of post-discharge VTE prophylaxis among hospitalized patients with IBD. Methods: A decision tree was used to compare inpatient prophylaxis alone versus 4 weeks of post-discharge VTE prophylaxis with rivaroxaban 10 mg/day. Our primary outcome was quality-adjusted life years (QALYs) over one year, and strategies were compared using a willingness to pay of $100, 000/QALY from a societal perspective. Costs (in 2020 $US), incremental cost-effectiveness ratios (ICERs), and number needed to treat (NNT) to prevent one VTE and VTE death were calculated. Deterministic 1-way and probabilistic analyses were performed to assess uncertainty within the model. Results: Four-week post-discharge prophylaxis with rivaroxaban resulted in 1.68 higher QALYs per 1000 persons and an incremental cost of $185, 778 per QALY as compared to no post-discharge prophylaxis. The NNT to prevent a single VTE was 78 individuals, while the NNT to prevent a single VTE-related death was 3190 individuals. One-way sensitivity analyses showed that higher baseline VTE risk >4.5% or decreased cost of rivaroxaban ≤$280 can reduce the ICER to <$100, 000/QALY. Probabilistic sensitivity analyses favored post-discharge prophylaxis in 26.5% of iterations. Abbreviations: QALY (Quality-Adjusted Life Years), ICER (Incremental Cost-Effectiveness Ratio), NNT (Number Needed to Treat), VTE (Venous Thromboembolism) Figure. Tornado diagram showing main drivers (variables and sensitivity ranges) of the incremental cost-effectiveness ratio (ICER). *Values represent threshold values that reduce the ICER to <$100, 000/QALY. Abbreviations: VTE (Venous Thromboembolism), DVT (Deep Vein Thrombosis), PE (Pulmonary Embolism), PTS (Post-Thrombotic Syndrome), WTP (Willingness To Pay), EV (Expected Value) Conclusion: Four weeks of post-discharge VTE prophylaxis results in higher QALYs as compared to inpatient prophylaxis alone, and can prevent one post-discharge VTE among 78 patients with IBD. As such, post-discharge VTE prophylaxis in patients with IBD should be considered in a case-by-case scenario considering VTE risk profile, costs, and patient preference.